2022
DOI: 10.3390/fishes7030137
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Fructooligosaccharides in Diets Influence Growth Performance, Digestive Enzyme Activity, and Expression of Intestinal Barrier Function Genes in Tropical Gar (Atractosteus tropicus) Larvae

Abstract: This study was conducted to investigate the effects of dietary fructooligosaccharides (FOS) on the growth, survival rate, digestive enzyms activity, and the expression of intestinal barrier function genes in tropical gar (Atractosteus tropicus) larvae. A total of 960 larvae (0.030 ± 0.006 g) were fed three diets supplemented with increasing FOS concentrations (2.5, 5, and 7.5 g kg−1) and a control diet for 15 days. Results revealed that a 7.5 g kg−1 FOS supplementation improved weight gain, specific growth rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 47 publications
(70 reference statements)
0
0
0
Order By: Relevance
“…Our study showed a higher expression of this gene in the intestine of A. tropicus juveniles with 1.5% SP. Similar results were reported by Pérez-Jiménez [43], who found a greater expression of muc2 when increasing the concentrations of FOS (7.5%) in larvae of A. tropicus. Other components of the intestinal barrier include the tight junctions (TJs), which provide a barrier within the membrane by regulating paracellular permeability and protein diffusion, thus maintaining cell surface polarity and enhancing the transportation of proteins and macromolecules through cells [44].…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed a higher expression of this gene in the intestine of A. tropicus juveniles with 1.5% SP. Similar results were reported by Pérez-Jiménez [43], who found a greater expression of muc2 when increasing the concentrations of FOS (7.5%) in larvae of A. tropicus. Other components of the intestinal barrier include the tight junctions (TJs), which provide a barrier within the membrane by regulating paracellular permeability and protein diffusion, thus maintaining cell surface polarity and enhancing the transportation of proteins and macromolecules through cells [44].…”
Section: Discussionsupporting
confidence: 90%
“…The effect of the T1 (feeding the fish YJB continuously) and T2 (feeding them YJB for 1 day and the basal diet on the following day) treatments on growth (FBW, WG, and SGR), feed utilization (FC, FE, and PER), and digestive enzyme activity showed a significant difference from that of the T0 treatment (feeding the fish a basal diet continuously). FOSs, a prebiotic present in YJB, are implicated in the digestion, absorption, and metabolism of essential nutrients in aquatic animals [35][36][37][38][39]. The growth performance of blunt snout bream (Megalobrama amblycephala) administered 4 g kg −1 of FOSs discontinuously was better than that of a control group fed a basal diet continuously but was not significantly different from that of fish fed 4 g kg −1 of FOSs continuously [39].…”
Section: Discussionmentioning
confidence: 97%
“…In studies using FOS in concentrations of 0.5-2.0%, Sepúlveda-Quiroz et al [99] noted increased growth and a significant reduction in protease, trypsin, and lipase activities. While Pérez-Jiménez et al [100] found significant increases in protease and amylase activities. Regarding the use of inulin, De La Cruz-Marín et al [101] defined an increase in survival at a concentration of 2.5% after 45 days of the experiment.…”
Section: Use Of Prebiotics In Mexican Fish Aquaculture Experimentsmentioning
confidence: 91%